Executive Remuneration and Corporate Governance in the Contemporary UK Corporation. - Pugla, Varun (2007)
Executive remuneration has attracted much attention from investors, financial economists, regulators, the media and the public at large. For the past 20 years the subject of executive remuneration was dominated by stock based compensation. Annual bonuses as a component in executive remuneration were relatively neglected. In the current scenario stock based compensation has started loosing its importance due to complexities involved and slow progress in stock markets. Companies have now started focusing more on annual bonuses as an incentive pay. This paper provides an overview of annual bonus landscape and corporate governance practices in the UK. An attempt has been made to address the issues related to annual bonuses and fill the gap which has existed for a long time in the studies related to executive remuneration. This paper uses FTSE 100 index to examine the level of transparency adopted by the companies. A sample of 20 companies was chosen using transparency and disclosure policy of annual bonuses as a base. These companies were then tested for pay-performance relationship and governance features. The results indicate that the companies with high transparency have better pay-performance relationship, however, in terms of governance features (such as substantial shareholding, proportion of non-executive directors, board size) companies with medium-low transparency were head to head with the companies in high transparency category.